The relationship between virtual reality attitudes and metaverse in university students - Mustafa Koc; Efecan Tezcan; Zeynep Hazal Ulutas; Mustafa Ayhan (Ozlem Book Center, 2024)
Virtual reality affects teaching and learning processes in the classroom. Metaverse is a simulated virtual environment that includes virtual reality and augmented reality. The aim of this research is to determine the attitudes of Sports Science students towards the concepts of virtual reality and metaverse and to reveal the relationship between these two scales. The sample of the research consists of students (n=205) studying at Gümüşhane University School of Physical Education and Sports (Türkiye), determined by the easily accessible case sampling method. Data collection consists of questions about students' gender, age, income, virtual reality or metaverse experience, and time spent on the internet. The Virtual Reality Attitude Scale and the Metaverse Scale were used. The study, which was handled from a quantitative perspective, used the relational-scanning method. Data were collected through face-to-face surveys. SPSS 29.0 package program was used to analysys. Independent Samples T Test was used for gender, age and experience, and One-Way Analysis of Variance for Independent Samples (ANOVA) was used for income and time spent on the internet. Analysis results; It was interpreted with test statistics and p values, significance was based on p ≤ 0.05. The eta-squared formula was used to calculate the effect size. In evaluating the relationship between the two scales, Pearson Product Moment Correlation Coefficient was used and the significance value was accepted as 0.05. As a result, there were no differences in attitudes towards virtual reality and metaverse applications according to gender, personal income and time spent on the internet during the day. Having previously experienced virtual reality or metaverse revealed significant differences in both scales. Having the experience positively affects the attitude towards the concepts of virtual reality and metaverse. Finally, the relationship between the used scales was evaluated and it was seen that these two concepts moderately affected each other.